(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This scientific article describes the specific features of increasing the income of the population in the region, the tasks to be performed, and the objects of development of this area. The purpose of writing this article: To liberalize the economy in our country, to transfer the main part of the tasks of the republic’s central management bodies to local authorities and self-government bodies, and to carry out many works on increasing their powers. Result: development of strategies for promotion and development of this sector in our country.